Toxicity and modulation of silver nanoparticles synthesized using abalone viscera hydrolysates on bacterial community in aquatic environment - Zhang, Yue; Yang, Zhuan; Ni, Jing; Ma, Ying; Xiong, Hejian; Jian, Wenjie (Frontiers in Microbiology, 2022)
Polysaccharide decorated silver nanoparticles (AgNPs) are a new type of antibacterial agent in aquaculture, but their effects on the bacterial community structure in aquaculture water are still unknown. In this study, the primary hydrolysate from abalone (Haliotis discus hannai) viscera (AVH) was used to biosynthesize AVH-AgNPs by insitu reduction, and the crystallinity nature, size, morphology and chemical composition were analyzed by high resolution characterization techniques such as Ultraviolet-visible spectroscopy (UV-vis), X-rays diffraction (XRD), Transmission Electron Microscope (TEM), Dynamic light scattering (DLS), Zeta potential, inductively coupled plasma-optical emission spectrometry (ICP-OES) and Turbiscan stability index (TSI) values. Furthermore, the acute toxicity of AVH-AgNPs to zebrafish (Danio rerio) and their effects on bacterial community structure in fish culture water at low concentrations were studied. The results showed that the spherical AVH-AgNPs with an average diameter of 54.57 ± 12.96 nm had good stability, low toxicity, and good in vitro antibacterial activity. Within the experimental concentration range, all AVH-AgNPs treatments had decreased the bacterial diversity in zebrafish culture water to varying degrees. The bacteria with significantly decreased abundances were pathogenic or potential pathogenic, such as Aeromonas veronii, Flavobacterium columnare, and genera Flectobacillus and Bosea. The abundance of Haliscomenobacter sp. JS224, which might cause sludge swelling, also decreased significantly. On the other hand, the relative abundance of some bacterial taxa could remove xenobiotics (e.g., Runella defluvii and Phenylobacterium), control water eutrophication (Sediminibacterium), and reduce toxic algae proliferation (Candidatus Intestinusbacter nucleariae and Candidatus Finniella), increased significantly. Thus, the application of AVH-AgNPs in aquaculture water at low concentrations is relatively safe and has positive significance for improving the aquaculture environment. Also, AVH-AgNPs have good prospects in aquaculture.